"Epileptic winds and breezes": Coleridgean Fancy and the Pathology of the Mind. Issue 2 (October 2019) - Page-Jones, Kimberley
Abstract : This article focuses on Coleridge's writing of epileptic signs in the light of debates and disagreements regarding the physiology and psychology of the brain by, among others, Erasmus Darwin, and Beddoes. Widely debated at a time where both evangelical movements and consumer behaviours were threatening the nerves and brains of English society, epileptic auras, I suggest, formed a significant context for Coleridge's pathography writing: his understanding of epileptic signs influenced his theory of a poetic mind involuntarily creating stories and fictions that could be disbelieved and thus disavowed.